The effect of surface charge and KNO3 additive on the crystallization of potassium chloride - Ceyhan, Ayhan Abdullah; Bulutcu, A. Nusret (Elsevier BV, 2011)
Abstract In this study, crystal growth and dissolution rates of potassium chloride crystals in pure solution and in the presence of potassium nitrate were investigated in a stagnant type single crystal cell using an image analyzer system. Closely sized seed crystals were separated with respect to their surface potentials using an electrostatic separator and then growth and dissolution behavior of potassium chloride crystals having different surface charges were systematically measured in pure solution and at 10, 100 and 1000 ppm additive concentrations at around 20 °C. In high supersaturation levels, very thin but very long rod-like growth, growing perpendicular to the surface, were observed. This is considered to result from surface nucleation. A dead zone was detected and its width was a function of surface potential of seed crystals. It was determined that, potassium nitrate additive, which has a common ion with KCl leads to increase the surface potential but not to affect the growth behavior, significantly.
Keywords: Growth from solutions; Single crystal growth; Surface structure; Additive; Dendrites; Potassium compounds